Sheaves of measures and KMS-weights on topological graph algebras - Eidesen, Jonas (MATHEMATICA SCANDINAVICA, 2024)
We show that the collection of regular Borel measures on a second-countable locally compact Hausdorff space has the structure of a sheaf. With this we give an alternate description of the pullback of a regular Borel measure along a local homeomorphism. We are able to use these tools to give a description of the KMS_β -weights for the gauge-action on the graph C^*-algebra of a second-countable topological graph in terms of sub-invariant measures on the vertex space of said topological graph.